2017
DOI: 10.1177/0890334416682007
|View full text |Cite
|
Sign up to set email alerts
|

An Adoptive Mother Who Became a Human Milk Donor

Abstract: Inducing lactation in the absence of pregnancy (nonpuerperal lactation) is not always successful and, in many cases, only partial breastfeeding is achieved. Different protocols have been described, but scientific evidence and research are lacking in this area. The authors describe the case of a woman with a history of a miscarriage, for whom the lactation induction process was so effective that she became a milk donor even before she received her adopted child. She had not previously used hormone treatment. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
1
13
0
8
Order By: Relevance
“…For women who have not previously breastfed, this process is called “induced lactation.” If they have previously breastfed, it is termed “relactation” (WHO, 1998). Mothers often decide to undergo induced lactation or relactation to strengthen the mother–child bond (Flores-Antón, García-Lara, & Pallás-Alonso, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For women who have not previously breastfed, this process is called “induced lactation.” If they have previously breastfed, it is termed “relactation” (WHO, 1998). Mothers often decide to undergo induced lactation or relactation to strengthen the mother–child bond (Flores-Antón, García-Lara, & Pallás-Alonso, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lommen and Brown (2015) concluded that the support that women received from breastfeeding services and their families enabled them to breastfeed their babies and face feelings of rejection, anger, stress, and failure. Flores-Antón et al (2017) described a mother who managed to feed her adopted baby exclusively with her own milk and argued that motivation and confidence helped her succeed.…”
Section: Introductionmentioning
confidence: 99%
“…It was important to consider the woman's priorities and the particular family configuration Szucs et al, 2010;Wilson et al, 2015;Cazorla-Ortiz et al, 2020). This kind of support could be offered by an International Board Certified Lactation Consultants (Biervliet et al, 2001;Cazorla-Ortiz et al, 2020;Farhadi & Philip, 2017;Flores-Antón et al, 2017). In the report by Kirkman and Kirkman (2001) concerning a case of surrogate motherhood between two sisters, the support the sisters offered one another was what enabled them to continue with the induction process, despite the difficulties they encountered along the way.…”
Section: Factors Associated With the Mother's Satisfactionmentioning
confidence: 99%
“…Frequent Stimulation. Each breast had to be stimulated for 10-20 min, 4-10 times a day (including at night), and this could be done manually or by using a breast pump, or both (Banapurmath et al, 1993;Cazorla-Ortiz et al, 2020;Flores-Antón et al, 2017;LeCain et al, 2020;McGuire, 2018;Reisman & Goldstein, 2018;Szucs et al, 2010;Wilson et al, 2015). In the study by Lakhkar (2000), four (33.3%) of the 12 participants who began the process of induced lactation did not produce milk.…”
Section: Factors Associated With the Mother's Satisfactionmentioning
confidence: 99%
“…There has been some literature documenting the induction of lactation in cisgender womenindividuals who were assigned female sex at birth and identify as a womanin cases of adoption or surrogacy [3][4][5][6][7]. These protocols include the use of high estradiol and progesterone levels with later reduction to simulate birth, a galactagogue, and a breast pump for regular interval nipple stimulation [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%